Biomineralized synthesis of luminescent protease-(NH4)2Y3F11•H2O hybrid nanospheres and their applications as a stable and reusable enzyme reactor - Wenyu Wei; Manman He; Jianrui Ma; Huixia He; Peng Liu; Jianxi Xiao (Collagen and Leather, 2024)
Abstract Proteases, such as trypsin, are essential for extracting collagen in various industrial applications. The potential applications of rare earth nanomaterials, specifically yttrium nanoparticles, have attracted significant interest across various fields due to their distinctive characteristics, including high dielectric constant and thermal stability. Biomineralization has emerged as a promising approach to synthesize protein-inorganic nanomaterials with hierarchical structures and desired functions. In the present investigation, a novel protease-templated biomineralization strategy was developed for synthesizing protease-(NH4)2Y3F11•H2O hybrid nanomaterials using a one-pot method under very mild conditions. For modifying the morphologies of (NH4)2Y3F11•H2O throughout biomineralization, protease has been demonstrated to be a highly promising biotemplate. Protease was utilized as a template for morphological control in the biomineralization procedure, which resulted in a gradual transformation of the initially formed (NH4)2Y3F11•H2O octahedral structures into uniform nanospheres. The applicability of this approach was supported by successfully utilizing various proteases to synthesize protease-(NH4)2Y3F11•H2O hybrid nanospheres. In addition to a strong and desirable luminescent signal, these hybrid nanospheres demonstrated extensive recycling because of their high enzymatic activity, stability and durability. The protease-mediated biomineralization approach offers an easy and robust approach to develop innovative protease-inorganic composites. Its moderate reaction conditions and simple operation render it a viable tool for developing stable and reusable enzyme reactors in various industrial applications. Graphical Abstract